Productivite et potentialites des systemes pastoraux - Cossins, N.J. (1985)
Examines the productivity of East African pastoral systems in terms of animal protein & energy production, milk offtake and livestock production parameters such as calving percentage, calf mortality and herd structure; compares the productivity of East African pastoral systems to those of commercial ranches and to pastoral systems in other parts of the world.